INTERNALISASI NILAI KEJUJURAN MELALUI KANTIN KEJUJURAN (STUDI PADA JURUSAN AKUNTANSI POLITEKNIK NEGERI PONTIANAK) - Riyadhi, Baidhillah; Mujahidah, Nelly (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2020)
The value of honesty is very important to be instilled in every individual. Honesty is one of the praiseworthy qualities that can bring humans to noble degrees. Every human being is recommended to maintain an honest character so that it is embedded into a permanent character not least in the campus world. The lecture process can be considered successful if it pays great attention to fostering honesty of students which is the ability to manage themselves (soft skills), in addition to scientific coaching and skills (hard skills) of the subjects being studied. This study aims to see how the internalization of the value of honesty can be done in various ways in the campus environment. This study uses descriptive qualitative methods, with grounded research design. Descriptive research method is a study that uses observations, interviews or questionnaires about the current situation, regarding the subject being studied. Descriptive method is used because this research tries to describe or describe the problems that occur at the present time. Internalization of honesty values in the Accounting Department is carried out through 3 (three) activities, namely: 1) pasting wisdom words about honesty at the classroom door. 2) film screening about honesty. 3) open an honesty canteen. Although only opened for 7 (seven) days, it can already be seen the honesty of students who shop at the honesty canteen. From the rotating capital and the benefits obtained, this activity can be continued.